2006
DOI: 10.3171/spi.2006.4.6.441
|View full text |Cite
|
Sign up to set email alerts
|

Pyogenic spinal infections and outcome according to the 36-Item Short Form Health Survey

Abstract: Object Pyogenic vertebral infections are rare. In most papers investigators have focused on risk factors, clinical characteristics, and diagnostic findings, and discussed different management strategies. The optimal strategy for dealing with spinal infections, however, remains controversial. Additionally, outcome data regarding quality of life (QOL) after pyogenic spinal infections are sparse. The aim of this study was to provide further data in this field.<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
45
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 23 publications
7
45
0
2
Order By: Relevance
“…Moreover, it primarily affects elderly patients in reduced states of health or with the accompanying risk factors mentioned above. Mean hospital stay has been reported as 30-49 days, and hospital mortality as 2-17% [2,7,21,36,43]. With our own patients, mean hospital stay is four weeks with a hospital mortality of 2%.…”
Section: Prognosismentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, it primarily affects elderly patients in reduced states of health or with the accompanying risk factors mentioned above. Mean hospital stay has been reported as 30-49 days, and hospital mortality as 2-17% [2,7,21,36,43]. With our own patients, mean hospital stay is four weeks with a hospital mortality of 2%.…”
Section: Prognosismentioning
confidence: 98%
“…In addition, quality of life for all patients was far lower than that of a normal population. Slightly improved quality of life and significantly higher levels of patient satisfaction were found in the surgicallytreated patients [43]. In a group of 25 spondylodiscitis patients, Lerner et al identified an improvement of neurological deficits for 76% after a mean of 2.6 years, while 20% showed no change.…”
Section: Prognosismentioning
confidence: 99%
“…After a surgical debridement and subsequent 4 weeks of intravenous antibiotic therapy, the patients underwent autogenous bone grafting and anterior plating. Since then, several series have been presented with patients undergoing anterior corpectomy and plate fixation [10,15,24,30,37,38,44,48,51], but the number of patients enrolled in these studies was relatively small and most of them were cervical cases.…”
Section: Discussionmentioning
confidence: 99%
“…5,6,10,13,14 The overall mortality of spondylodiscitis is 5-10%, [2][3][4]7,15 but studies reporting outcome after surgical treatment are scarce, and few studies have reported the health-related quality of life (HRQL) after surgery. [16][17][18][19][20] A few studies have shown that a preoperative neurological deficit is a predictor of a negative outcome, 4,8,9 and neurological deficits are more often present when the spinal infection affects the cervical or thoracic regions. 8 No studies so far have examined HRQL in these groups.…”
Section: Introductionmentioning
confidence: 99%